Photon Distribution of Sole-Source Lighting Affects the Mineral Nutrient Content of Microgreens - Viktorija Vaštakaitė-Kairienė; Aušra Brazaitytė; Jurga Miliauskienė; Rūta Sutulienė; Kristina Laužikė; Akvilė Viršilė; Giedrė Samuolienė; Erik S. Runkle (Agriculture, 2022)
In the study, we cultivated basil, beet, and mustard microgreens under different lighting treatments from light-emitting diodes (LEDs) and evaluated the contents of mineral nutrients. Microgreens grew under blue 447, red 638 and 665, far-red 731 nm LEDs, or the same spectrum but with partial substitution of 638 nm red with green 520 (BRG), yellow 595 (BRY), or orange 622 nm (BRO) LEDs (16 h photoperiod; total photon flux density of 300 μmol m −2 s −1). BRG, BRY, or BRO lighting had distinct effects on mineral contents among the microgreen species. BRG increased the content of mineral nutrients, especially in mustard and beet. In all microgreens, Ca and P were associated with BRG; in beet and mustard, Zn and Mg were associated with BRG; in basil, Zn was associated with BRY and Mg with BRO treatments. A broader photon spectrum increased Fe (up to 2.9–fold), K:Ca, P:Mg, and P:Zn in basil, and Fe:Zn in microgreens. We conclude that the partial replacement of red with green light was the most effective at enhancing the mineral nutrient content of microgreens, although responses varied among the crops studied.